This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Better way:
( 1 + x ) x = e x ln ( 1 + x )
x → 0 lim x 2 ( 1 + x ) x − 1
= x → 0 lim x 2 e x ln ( 1 + x ) − 1
= x → 0 lim x 2 x ln ( 1 + x ) = x → 0 lim x 2 x 2 = 1
Using t → 0 lim e t − 1 = t , t → 0 lim ln ( 1 + t ) = t
Log in to reply
Possibly a faster way is the following:
x → 0 lim x 2 ( 1 + x ) x − 1
As x → 0 , we have that ( 1 + x ) n = 1 + n x
x → 0 lim x 2 1 + ( x ) x − 1
x → 0 lim x 2 x 2 = 1
Good solution bro.
( 1 + x ) x − 1 = e ln ( 1 + x ) x − 1 = e x 2 + o ( x 2 ) − 1 = x 2 + o ( x 2 ) so that the limit is 1
We are using the Taylor series ln ( 1 + x ) = x + o ( x ) and e x = 1 + x + o ( x )
Here we say that a function f ( x ) is o ( x k ) if lim x → 0 x k f ( x ) = 0
(1+x)n =1+nx if x is very small ∴ (1+x)x =1+x2 ∴lim x->0 ((1+x)x -1)/x2 =x2/x2=1
Problem Loading...
Note Loading...
Set Loading...
The Limit is in the Indeterminate Form 0 0
Applying L'Hopital's Rule Yields :
lim x → 0 x 2 ( 1 + x ) x − 1
= 2 x [ ( 1 + x ) x ] ′
= lim x → 0 2 x ( 1 + x ) x ln ( 1 + x ) + x ( 1 + x ) x − 1
= lim x → 0 ( 1 + x ) x ⋅ 2 1 ⋅ x ln ( 1 + x ) + lim x → 0 2 ( 1 + x ) x − 1
= 1 ⋅ 2 1 ⋅ 1 + 2 1 = 1
Thus Answer Is 1
⋯ ⋯ ⋯ ⋯ ⋯
Note That
[ ( 1 + x ) x ] ′ = [ e x ln ( 1 + x ) ] ′
= e x ln ( 1 + x ) ⋅ [ x ln ( 1 + x ) ] ′
= ( 1 + x ) x ( ln ( 1 + x ) + x + 1 x )
= ( 1 + x ) x ln ( 1 + x ) + ( 1 + x ) x − 1 x